Sulcoflex Piggyback Intraocular Lens Implantation For Correction Of Refractive Errors Following Cataract Surgery - Purba, Mona; Mardinger, Cynthia; Hibma, Abby; Gimbel, Howard V (Canadian Journal of Optometry, 2016)
Purpose: To investigate the visual and refractive outcomes following implantation of a Sulcoflex intraocular lens (IOL) to correct pseudophakic refractive error. Methods: This retrospective chart review included 14 pseudophakic eyes of 13 patients who underwent implantation of a Sulcoflex IOL. The Sulcoflex IOL is a piggyback IOL technique where a secondary, supplementary lens is implanted in the ciliary sulcus. Results: Eleven eyes (78.6%) had a postoperative SE within 0.50 D of the targeted SE. Preoperative UDVA was 20/30 in 4 eyes (28.6%), and 20/40 or worse in 10 eyes (71.4%). Postoperative UDVA was 20/30 or better in all eyes, where half (50.0%) of eyes were 20/20 or better. The mean preoperative logMAR (0.50 ± 0.33) significantly improved to 0.06 ± 0.09, p<.01. There were no complications. Conclusions. The significant improvement in UDVA and the precision in reaching the target refraction suggest that the Sulcoflex is a viable and successful treatment option for pseudophakic refractive error.